Universal Access in Urban Areas : Why Universal Access in Urban Areas Matters for Sustainable Mobility - Mason, Jacob; Turner, Philip; Steriu, Mircea (World Bank, Washington, DC, 2018)
As one of the four global goals framing sustainable mobility in the Global Mobility Report (GMR),universal access in urban areas is the ability for people to reach the destinations necessary to lead productive and fulfilling lives. But transport infrastructure and services are rarely distributed equitably, and ensuring equity of access is of paramount importance. By 2050, the world’s urban population is expected to grow by 2.5 billion people, reaching 66 percent of the total global population. Most urban growth is projected to take place in developing countries inAfrica and Asia. As economic activity continues to shift from mature economies toward these emerging markets, the number of daily trips made by people in urban areas could increase by 50 percent between 2005 and 2025. The GMR positioned access to economic and social opportunities for everyone as a key goal for achieving sustainable mobility, regardless of income, gender, age, disability status, and geographical location. The Global Tracking Framework (GTF) proposes indicators to measure progress toward that goal. This work supports Sustainable Development Goals 9 and 11 and the Habitat III New Urban Agenda.